Quantum and Optoelectronic Devices, Circuits and Systems (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The fields of quantum electronics (e.g., quantum dots and superconducting circuits) and optoelectronics have garnered much interest in the past few years. They deal with quantum and optical platforms in combination with electronic and condensed matter systems, which may serve as building blocks for a plethora of applications in quantum computing and optical technology.In this reprint, we reprint the articles of the Special Issue "Quantum and Optoelectronic Devices, Circuits and Systems", published in Electronics (MDPI).